Design optimization of a well-known geometry for minimum weight utilizing the Density-Shape-Element Removal method (D-S-ER) - Teke, Ibrahim T.; Ertas, Ahmet H. (EDP Sciences, 2024)
The development of topology optimization (TO) methods gives designers new capabilities. A variety of TO techniques have recently been used in special circumstances to expand the capabilities of generalist techniques on particular niche issues. To achieve more flexible solutions and generalized procedures for most of the problems, hybrid methods are in trend. Hence, in this study, a different application of the Density-Shape-Element Removal method (D-S-ER) has been used to reduce maximum stress while also significantly reducing the weight of the structure, a lifting hook. A raw model was taken into consideration for the procedure. The study's findings show that the suggested strategy can be employed to provide quick and effective solutions by means of optimizing the balance between weight and strength. One of the findings depicts that combining different methods could give flexibility even in well-proven geometry optimization, which is the lifting hook in this study. © 2024 EDP Sciences. All rights reserved.
2023 International Conference on Green Energy: Intelligent Transport Systems - Clean Energy Transitions, GreenEnergy 2023 -- 2023-11-22 through 2023-11-24 -- Kyiv -- 198585
Keywords: fatigue; hybrid topology optimization; lifting hook; structural analysis